Microstructure and optical loss in epitaxial (Pb,La)TiO3 thin films on (100) MgO - Kang, YM; Lee, KS; Baik, SG (GORDON BREACH SCI PUBL LTD, 1997)
Surface morphologies and microstructures of epitaxial (Pb1-xLax)TiO3 (PLT, x = 0.00, 0.08, 0.16, and 0.24) thin films grown on (100) MgO, have been investigated using various analytical techniques. Surface roughness of PLT films were measured by AFM and their domain structures were investigated by TEM and XRD. The surface roughness of the films varied severely with La concentration. For 0.08La-PLT film, very smooth surface has been achieved with 9.3 Angstrom of RMS roughness. Optical propagation losses of PLT films measured by prism coupling technique were 22.3, 6.0, 11.4, and 20.7 dB/cm for x = 0.00, 0.08, 0.16, and 0.24, respectively. Such a variation in optical losses seemed to be due to the surface morphology and abundance of domain boundaries that change continuous as a function of La concentration in the epitaxial PLT thin films.
Keywords: PULSED-LASER DEPOSITION; GROWTH